Incentivizing user provided connectivity for enhanced quality of service - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
Increase in the number of mobile users demanding Internet connectivity gave rise to a cooperative solution called User-provided connectivity (UPC) which is a promising paradigm to remedy Internet connectivity needs of mobile users. In this model participants cooperate to enable a group of mobile users to access Internet while they have no or limited connectivity. One of the key research problems in UPC is giving incentives to mobile network subscribers to promote active participation. In this work we propose a scheme to give incentives to mobile subscribers of a network assisted User Provided Network (UPN) in which subscribers with limited or no connectivity access Internet while still charging to their own quota. Our scheme proposes a simple and applicable bargaining based mechanism to encourage mobile network subscribers to join the protocol to provide UPC. Since the scheme is network assisted network operators are expected to support and do not impose any restrictions on the protocol. In this scheme utility and cost functions are defined for participants in terms of provided throughput and battery energy, and the protocol operates iteratively as in the case of a real world bargaining. © 2016 IEEE.
Keywords: bargaining; incentive design; network economics; sharing economics; User provided networks